Physician attitudes toward pharmaceutical sales representatives - Andaleeb, Syed Saad; Tallman, Robert R. (© 1995 Aspen Publishers, Inc., 2016)
This article was published in the Health Care Management Review [© 1995 Aspen Publishers, Inc. ] and The Journal's website is at: http://journals.lww.com/hcmrjournal/Abstract/1995/02030/Physician_attitudes_toward_pharmaceutical_sales.11.aspx